Penanaman Kemandirian Melalui Area Practical Life Metode Montessori Terhadap Anak Usia Dini - S, Nurindah; Rahmatia, Rahmatia; Hikrawati, Hikrawati (Jurnal Serambi Ilmu, 2026)
This study aims to determine how to instil early childhood independence through the Practical Life area with the application of the Montessori method at TKIT Al Hikmah Palopo. The research method used is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of six children aged 5-6 years who actively participated in Practical Life activities, children able to use 3 fingers when presenting tools, class teachers, Montessori teachers, and children's parents. The results showed that through Practical Life activities such as eating and drinking by themselves, sweeping, watering plants, and using polite words, children showed significant development in the aspect of independence. The application of the Montessori method, which emphasises directed freedom, exploration, and concrete activities, is proven to be able to encourage children to become more confident, responsible, and show independent behaviour. In addition, collaboration between teachers and parents plays an important role in maintaining the consistency of children's independence behaviour, both at school and at home. This research reinforces the relevance of the Montessori method as an effective approach in developing early childhood independence. Keywords ; Independence, Early Childhood, Practical Life, Montessori